Control of the compensating defects in Al-doped and Ga-doped ZnO nanocrystals for MIR plasmonics. Issue 46 (31st May 2017) - Hamza Taha, M. K.; Boisron, O.; Canut, B.; Melinon, P.; Penuelas, J.; Gendry, M.; Masenelli, B.
Abstract : The MIR plasmon of degenerate ZnO nanocrystals is tuned by the direct control of oxygen during their synthesis. Abstract : In degenerate semiconductor nanoparticles, the tuning range of the plasmon resonance is directly controlled by the electron gas concentration and thus by the dopant activation. Here, we investigate the improvement of the dopant activation in ZnO-based nanocrystals for mid IR plasmonics. For that purpose, we have synthesized Al-doped and Ga-doped ZnO nanocrystals in O-rich and O-poor environments. We show that the free carrier concentration can be doubled for the samples grown in an O-poor environment. Accordingly, the plasmon resonance shifts from 5 μm to 3.1 μm. In analogy with previous results from Ga-doped ZnO thin films, we discuss the effect of the possible reduction of the concentration of acceptor-like complexes such as AlZn –VZn and AlZn –Oi (resp. GaZn –VZn and GaZn –Oi ) on the activation improvement. Besides, whether long or rapid, thermal annealing does not improve the compensation ratio. Consequently, the control of O content during synthesis remains the most valuable tool to achieve the highest dopant activation in doped ZnO nanocrystals.